Correlation of metal ions with specific brain region volumes in neurodegenerative diseases - Melek, Ismet Murat; Kus, Berna; Kaptan, Zulal; Petekkaya, Emine (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2023)
There are reports stating that deteriorations in metal homeostasis in neurodegenerative diseases promote abnormal protein accumulation. In this study, the serum metal levels in Alzheimer's disease (AD) and Parkinson's disease (PD) and its relationship with the cortical regions of the brain were investigated.The patients were divided into 3 groups consisting of the AD group, PD group, and healthy control group (n = 15 for each). The volumes of specific brain regions were measured over the participants' 3-dimensional magnetic resonance images, and they were compared across the groups. Copper, zinc, iron, and ferritin levels in the serums were determined, and their correlations with the brain region volumes were examined.The volumes of left hippocampus and right substantia nigra were lower in the AD and PD groups, while the volume of the left nucleus caudatus (CdN) and bilateral insula were lower in the AD group compared to the control group. Serum zinc levels were lower in the AD and PD groups, while the iron level was lower in the PD group in comparison to the control group. In addition, the serum ferritin level was higher in the AD group than in the control group. Serum zinc and copper levels in the AD group were positively correlated with the volumes of the right entorhinal cortex, thalamus, CdN, and insula. Serum zinc and copper levels in the PD group showed a negative correlation with the left nucleus accumbens (NAc), right putamen, and right insula volumes. While the serum ferritin level in the PD group displayed a positive correlation with the bilateral CdN, putamen, and NAc, as well as the right hippocampus and insula volumes, no area was detected that showed a correlation with the serum ferritin level in the AD group.A relationship was determined between the serum metal levels in the AD and PD groups and certain brain cortical regions that showed volumetric changes, which can be important for the early diagnosis of neurodegenerative diseases.
Keywords: Male; Parkinson's disease; Iron; metal ions; Brain; Parkinson Disease; Neurodegenerative Diseases; Alzheimer's disease; Middle Aged; Magnetic Resonance Imaging; Zinc; Alzheimer Disease; Metals; Case-Control Studies; Ferritins; voxel-based morphometry; Humans; Female; Copper; Research Article; Aged